Grumpy monkey : ready, set, bananas! - Lang, Suzanne; Lang, Max, 1982- (New York : Random House, 2021)
Jim Panzee begrudgingly agrees to help Tortoise enter the big race.
Ages 4-6.
Grades K-1.
330L
Decoding demand: 57 (medium) Semantic demand: 54 (medium) Syntactic demand: 31 (low) Structure demand: 74 (high)
Keywords: Racing -- Juvenile fiction; Animals -- Juvenile fiction; Readers (Publications)